ҒӘРЕЗСИЗЛИК ЖЫЛЛАРЫНДА НӨКИС ҚАЛАСЫНЫҢ ТАРИЙХЫН ҮЙРЕНИЎДИҢ МЕТОДОЛОГИЯЛЫҚ ТИЙКАРЛАРЫ - Есназарова, З.; Алеуов, З. (FAN va JAMIYAT, 2021)
The article analyzes the methodological aspects of studying the history of the city Nukus over the years of independence, that is, its methods and methodology. When studying historical methodological analysis by experts, it was investigated the history of the city Nukus from scientific works of scientists in fundamental analysis. At the same time, preservation of the fundamental essence of Nukus is to ensure the modern quality of education based on the current and future needs of the individual, society and goverment.